Optimization study to improve filtration behaviour of electret filter media. Issue 11 (1st November 2016) - Thakur, Rashmi; Das, Dipayan; Das, Apurba
Abstract : This work reports on a study of air filtration behaviour of electret fibrous filter media prepared from polymeric nonwoven materials using corona-charging process. In this work, a full factorial design of experiments in conjunction with response surface methodology of analysis was used. The single as well as interaction effects of fibre diameter, basis weight, point voltage and grid voltage on filtration efficiency were determined. The filtration efficiency was found to be higher with smaller fibre diameter, higher basis weight, higher point voltage and higher grid voltage. The fibre diameter contributed maximum towards the filtration efficiency, followed by the grid voltage, basis weight, and point voltage. A response surface model was developed to predict the filtration efficiency of the filter media. The model displayed very good correspondence with the experimental results. The experiments performed at the optimum levels of fibre diameter, basis weight, point voltage and grid voltage yielded filtration efficiency very close to the predicted value.